JUMPA Vol.3 No.1 Feb 2016 PENGARUH PRICE BOOK VALUE, OPERATING PROFIT MARGIN, EARNING PER SHARE, DEBT TO EQUITY RATIO DAN RETURN ON EQUITY TERHADAP HARGA SAHAM PERUSAHAAN DI BURSA EFEK INDONESIA (STUDI PADA SAHAM PERUSAHAAN LQ-45): PENGARUH PRICE BOOK VALUE, OPERATING PROFIT MARGIN, EARNING PER SHARE, DEBT TO EQUITY RATIO DAN RETURN ON EQUITY TERHADAP HARGA SAHAM PERUSAHAAN DI BURSA EFEK INDONESIA (STUDI PADA SAHAM PERUSAHAAN LQ-45) - Riska Damayanti Sekolah Tinggi Ilmu Ekonomi Y.A.I. Jakarta (Sekolah Tinggi Ilmu Ekonomi Y.A.I - Jakarta - Indonesia, 2016)
This aim of study is to investigate many perceptions from older studies related to inconsistency of study result in regard to influence of fundamental factors on stock prices. Furthermore, this study is test and determine empirically about the influence of PBV, OPM, EPS, DER and ROE on stock prices that contained in LQ 45 registered company in Indonesia Stock Exchange 2009 – 2013. This study technique is nonprobability sampling or non-random sample selection method, i.e. Purposive Sampling in data collecting. The study population is all recorded issuers in LQ 45 index. The sample study is 38 registered companies in LQ 45, who meet the criteria and terms of financial statement presentation. Study data is secondary data obtained through the data collecting. The data analysis is classical assumption test, partial regression coefficient test, simultaneous significance test and hypotheses test using correlation test, determination coefficient test and analysis regression panel test with reviews method. This study contains six hypotheses, from six hypotheses proposed, all of them accepted. These hypothesis test result indicates that PBV, OPM, EPS, DER, ROE and jointly have significant effect on stock prices. For the simultaneous analysis result indicates significant value 0,000 which means that PBV, OPM, EPS, DER, ROE have influence jointly/simultaneously on stock prices. But partially there is one variable that has no effect on stock prices, i.e. ROE, while the variables of PBV, OPM, EPS and DER have significant influence on stock prices. And from this study result, the conclusion is that the ability from all independent variables jointly influenced the dependent variable by 92.05%, i.e. PBV, OPM, EPS, DER, ROE jointly influenced on stock prices. This study also support the previous study that is conducted by Evi Octavia (2007), Bram Hardianto (2008), Lisandri, Rabiatul Adawiyah (2013) where PBV, OPM, EPS, DER, and ROE influence on stock prices.